THE BENEFITS OF INTEGRATING ENGLISH TEACHING WITH OTHER SUBJECTS - Aziza Nurbek qizi Sobirova; Dilfuza Khudaykul kizi Iskandarova (World Scientific Research Journal, 2025)
This article examines the integration of English language teaching with other subjects (CLIL), focusing on its impact on language acquisition, academic performance, motivation, and critical thinking. It explores methodologies, evaluates their effectiveness, and addresses challenges educators face. Through research and case studies, the study highlights the pedagogical benefits of interdisciplinary teaching, showing how it enhances linguistic competence, subject knowledge, and cognitive engagement.